Bilateral hematoma of sternocleidomastoid muscles. A case presentation. - Zoe Quintero Delgado; José Julio Requeiro Molina (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
Presentation of the case of an infant with bilateral congenital torticollis which development was followed by ultrasound. Homeopathy and physiotherapy were used for its treatment. This is an infrequent disease scarcely reported in medical literature.